2017
DOI: 10.1111/cmi.12731
|View full text |Cite
|
Sign up to set email alerts
|

A fibronectin-binding protein (FbpA) of Weissella cibaria inhibits colonization and infection of Staphylococcus aureus in mammary glands

Abstract: Staphylococcus aureus (S. aureus) is a frequent cause of infections in both humans and animals. Probiotics are known to inhibit colonization of pathogens on host tissues. However, mechanisms for the inhibition are still elusive due to complex host-microbe and microbe-microbe interactions. Here, we show that reduced abilities of S. aureus to infect mammary glands in the presence of Weissella cibaria (W. cibaria) were correlated with its poor adherence to mammary epithelial cells. Such inhibition by W. cibaria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
(78 reference statements)
0
26
0
Order By: Relevance
“…Another promising candidate used for mastitis treatment is the Bac2A derivative IDR-1018 (VRLIVAVRIWRR); it showed potent activity against S. aureus (MIC, 5 μg/ml) and significantly reduced the LPS-induced pro-inflammatory response, indicating that it is one of the strongest synthetic immunomodulatory peptides. These characteristics make IDR1018 an ideal candidate for the treatment of mastitis 44,45 . However, there are some limitations associated with its use, such as expensive production costs, in vivo instability, and some cytotoxicity at high concentrations; further studies are required to fully understand and evaluate the biological significance of these peptides 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising candidate used for mastitis treatment is the Bac2A derivative IDR-1018 (VRLIVAVRIWRR); it showed potent activity against S. aureus (MIC, 5 μg/ml) and significantly reduced the LPS-induced pro-inflammatory response, indicating that it is one of the strongest synthetic immunomodulatory peptides. These characteristics make IDR1018 an ideal candidate for the treatment of mastitis 44,45 . However, there are some limitations associated with its use, such as expensive production costs, in vivo instability, and some cytotoxicity at high concentrations; further studies are required to fully understand and evaluate the biological significance of these peptides 45 .…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics make IDR1018 an ideal candidate for the treatment of mastitis 44,45 . However, there are some limitations associated with its use, such as expensive production costs, in vivo instability, and some cytotoxicity at high concentrations; further studies are required to fully understand and evaluate the biological significance of these peptides 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus E48, a clinical mastitis isolate, had been used to induce mouse mastitis model ( Wang et al, 2017 ). Tetracycline is one of the most extensively used antibiotics for mastitis treatment because of its relative safety, low cost, and a broad-spectrum activity ( Kuang et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Other non-classical proteins exposed on the cell surface of parietal monoderm bacteria are known as fibronectin-binding proteins (FBPs) characterised by two adjacent conserved domains: the about first 400 amino acids (PF05833) of which 89 residues associate with fibronectin-binding activity ( Courtney et al, 1994 ) followed by the conserved domain of unknown function DUF814 (IPR008532) of ∼100 amino acid residues including conserved motif (D/E)X(W/Y)XH. First identified in the fibronectin-binding protein FBP54 of S. pyogenes ( Courtney et al, 1994 ), these domains have been reported in PavA of S. pneumoniae ( Holmes et al, 2001 ), FbpA of Streptococcus gordonii ( Christie et al, 2002 ), Fbp68 of C. difficile ( Hennequin et al, 2003 ), FbpB of Clostridium perfringens ( Katayama et al, 2009 ), EfbA in E. faecalis ( Torelli et al, 2012 ), Fnm in E. faecium ( Somarajan et al, 2015 ), YloA in B. subtilis ( Rodriguez Ayala et al, 2017 ) and FbpA in Weissella cibaria ( Wang et al, 2017 ). Consistently with impaired binding capacity to fibronectin upon nested deletions of the C-terminal part of S. pneumoniae PavA ( Holmes et al, 2001 ), structural and functional analyses of FBPS of Streptococcus suis revealed that the C-terminal half of FBPs mediates binding to fibronectin whereas the N-terminal half interacts specifically with the surface of Streptococcus suis ( Musyoki et al, 2016 ).…”
Section: Cell-surface Proteins Localised At the Cell Wall (Go: 000927mentioning
confidence: 96%